IMPLEMENTATION OF ISLAMIC LAW ON THREE COUNTRIES (STUDY OF COMPARISON ON INDONESIA, MALAYSIA, AND BRUNAI DARUSALAM) - Fitri Rafianti (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The application of Islamic law to a heterogeneous country is very difficult, especially if the country has a law or a law which is considered able to cover all religious believers in the country, in this case the comparative approach of law is used as a method of research and science His age is relatively young, because it only grew rapidly in the late XIX century or early XX century. Comparison is one of the most important sources of knowledge. Comparison can be said as a technique, discipline, implementation and method in which the values of human life, relationships and activities are known and evaluated. but in terms of Islamic law it is notonly referred to as a theory, but is a principle that must be enforced. Conceptually there are principles of Islamic law which include the arrangement and application of Islamic law for Muslims. Indonesia, Malaysia and Brunei Darussalam are countries that are known as the majority of the Muslim population and as a country that is known for the contribution of thought and application of Islamic Law to its system of government. only, because it is equally known that Indonesia, Malaysia, Brunei Darussalam are former colonies from the Netherlands and the United Kingdom. and the process of entry and development of Islamic teachings is through trade, and the most important of these three countries adheres to the government system and several regions still rooted in the royal system, Indonesia, which was formerly under Dutch colonization which is still trying to reduce Islamic law until a number of laws were formed which played a role in Islamic law, Malaysia which with the royal system and the ministry was in the grip of the British. the adoption of several Islamic laws contained in the authority of the religious council for the 8 legal systems contained in the rules of Islamic law, while the State of Brunei Darussalam which has implemented Islamic Law through 47 articles in the rules of the state and there are 29 articles containing elements of Islam.